Pendampingan Smart Home Anak Pemulung di Sekitar TPA Supit Urang Kota Malang - Antonius Alam Wicaksono; Nathasa Pramudita Irianti (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Supit Urang is a Final Waste Disposal Site (TPA) in the city of Malang. People living around the TPA use the Supit Urang TPA as a place to earn a living. There are children who are lazy every day to help their parents. As a result, children's motivation to learn becomes low to take education, especially school. This Community Service is carried out in the village of Mulyorejo, Malang City. The purpose of this service is to assist elementary school students in learning. This assistance is carried out with the Smart Home concept. The method implemented in this service program is mentoring for elementary school students, totaling 26 students. The results of Smart Home assistance are carried out by providing assistance in learning to read, write, and count. So that assistance provides benefits to improve the cognitive abilities of children around the Supit Urang TPA, Mulyorejo village, Malang City.